Female athlete triad coalition risk assessment tool is an evidenced-based tool that is reliable and well-described - De Souza, M. J.; Williams, N. I.; Koltun, K. J.; Strock, N. C. A. (Journal of Sports Sciences, 2020)
While the Triad Coalition CumulativeRisk Assessment Tool is an evidenced-based tool and provideswell-defined criteria for consistent utilization of the tool, thereare some limitations to the use of the tool. The limitations ofthe said tool include requiring access to DXA, accommodatingfor women who take hormone contraceptives, and challengesassociated with determining low energy availability/dietaryrestriction in thefield. As such, the authors (De Souza,Williams, and Koltun) have recently submitted a paper currentlyunder review to provide strategies for implementing the tool insuch situations when specific data (i.e., DXA BMD) cannot bedetermined and it is likely that the Female and Male AthleteTriad Coalition will provide updates to their tool in the nearfuture to accommodate these nuances. With respect to theRED-S tool, ambiguity regarding how to assess the individualrisk factors remains apparent, i.e., the RED-S authors do notprovide enough specific information for classification of riskfactors and therefore, different clearance decisions may result.It is recommended that this tool undergo revisions such that itcan be applied and interpreted consistently by users. It is alsorecommended that an evidenced-based approach be utilizedso that valid factors are used in the process of assessing risk.The path forward requires improvements to both tools, sinceassessing risk factors is an important step in ensuring thatathletes get proper care to prevent injury, especially to bone.